The evolution of Israeli public policy for drug-using backpackers - Hagit Bonny-Noach (BMC, 2018)
Abstract Background Over the past 20 years, the young-adult backpacking trip has emerged as a significant social phenomenon in Israeli society. This has received attention from scholars specializing in anthropology and tourism research, but only a few analytical studies exist on the drug policy processes and few provide Israeli social and health perspectives. The interaction of policymakers, media, and health deviancy is an important focus of inquiry. This study charts the establishment of a drug policy for Israeli backpackers. It covers the period from the emergence of the problem in the early 1990s until the present. Methods This study employs content analysis of newspaper articles and official documents, protocols, and reports written by policymakers and professionals. The latter were mostly produced by the Israel Anti-Drug Authority (IADA) and the Special Committee on Drug and Alcohol Abuse (SCDAA) in the Israeli Knesset. These are the two major Israeli agencies responsible for drug policy. Results Three periods in the establishment of backpacker drug policy can be identified. First period - until late 1995: No drug problem was recognized. The subject was not part of the public agenda. Even so, many backpackers were actually taking drugs. Second Period - late 1995 to 2000: The Israeli media started to report intensively on backpacker drug use. The issue then flared up into a significant 'social problem' demanding health and social solutions. In this phase, policymakers capitalized on a window of opportunity, and formulated a policy emphasizing prevention. Third period - from 2001 until the present: A sea change in institutional attitude occurred. In this period, drug-policy emphasis shifted from prevention to therapeutic-treatment approaches. As a result, harm reduction and unique treatment strategies were developed. Recommendations Policymakers should continue to improve health prevention, treatment, and harm reduction resources. It is recommended that the Ministry of Health set up consultation centers at clinics for travelers. These would provide support and assistance to backpackers before, during, and after their trips. The attention that Israel's drug policy for backpackers gives to prevention, treatment, and harm reduction is the first of its kind and unique. It can therefore serve as a model for other countries.